PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN NEARPOD PADA MATA PELAJARAN GEOGRAFI MATERI DINAMIKA LITOSFER DI KELAS X SMA NEGERI 5 GORONTALO - Meeradji, Hapsa; Eraku, Sunarty Suly; Masruroh, Masruroh (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
This study aims to develop a product in the form of Nearpod-assisted learning media that was developed. The research method uses Research and Development (R&D) with the ADDIE model approach (Analysis, Design, Development, Implementation, and Evaluation). The object of this study is Nearpod-assisted learning media for lithosphere dynamics material for class X IPS and geography subject teachers. The results of this study are that the development of Nearpod-assisted learning media has passed a validity test by product experts who got a percentage value of 84.28%, then a trial by material/content experts who got a percentage of 82.85% and finally by a validator learning expert who got a percentage of 90%. The results of student responses to Nearpod-assisted learning media in geography learning were tested twice, namely limited tests and general tests. The limited test on 15 students and got a result of 90.66%, while the general test on all 28 students got a result of 87.85%.